Postoperative acute kidney injury in lung transplant recipients. (10th January 2019) - Bennett, David; Fossi, Antonella; Marchetti, Luca; Lanzarone, Nicola; Sisi, Sauro; Refini, Rosa Metella; Sestini, Piersante; Luzzi, Luca; Paladini, Piero; Rottoli, Paola
Abstract: OBJECTIVES: Acute kidney injury (AKI) is a common postoperative complication after lung transplantation. The aim of the present study was to evaluate the incidence of AKI in lung transplant patients and its effect on patients and graft outcome in relation to degree of severity. METHODS: Data from 135 patients who underwent lung transplant in the same Italian institution were recorded retrospectively and analysed (69 unilateral and 66 bilateral lung transplants, age 51.2 ± 12.2 years, 84 males). RESULTS: One-third of our population developed AKI in the early postoperative period. Male sex and severe arterial hypotension with haemodynamic decompensation were significantly associated with an increased risk of AKI ( P = 0.025 and P = 0.002, respectively). Induction therapy with basiliximab and the use of tacrolimus instead of cyclosporine proved to be protective against AKI ( P = 0.047 and P = 0.004, respectively). Patients with AKI were sicker and showed a worse respiratory outcome with longer invasive mechanical ventilation ( P = 0.002), higher prevalence of tracheostomy ( P = 0.003) and need for postoperative extracorporeal membrane oxygenation ( P = 0.01) and required administration of vasoactive amine for a longer period ( P = 0.008). Patients with AKI showed a significantly lower survival rate than those who did not develop AKI ( P = 0.001). Patients with stage 3 AKI requiring renal replacement therapy had a worse survival rate ( P < 0.0001). CONCLUSIONS: Our study confirms the importance of AKI in patients undergoing lung transplant that can significantly affect outcome. The pathogenesis of AKI is heterogeneous, and prerenal causes have a great impact. Particular attention must be paid to the haemodynamics, which proved to be strongly associated with the onset of AKI. Severe renal impairment is associated with respiratory impairment and reduced survival.